The problems of Christian Ecological Ethics: aspects of research in the writings of John Paul II - Prysukhin, Sergiy (Ukrai͏̈ns'ke relihijeznavstvo, 2015)
The article of Prysukhin S. «The problems of Christian Ecological Ethics: aspects of research in the writings of John Paul II» analyzed the philosophical and theological writings of St. John Paul II, which reveal the essential characteristics of its ecological teaching, phenomenon, the role and importance of ecological ethics in the Christian system of values «culture of life».